Pengaruh Intelectual Capital terhadap Penerapan Corporate Governance - Tri Wahyudi; Gita Puspita (FEB Universitas Sultan Ageng Tirtayasa, 2020)
This research aims to determine the effect of intellectual capital on the implementation of corporate governance. The object of this research is a Sharia Commercial Bank in Indonesia and registered at Bank Indonesia in the period 2011-2016. The number of samples is determined based on the criteria (purposive sampling), so 57 ( fifty seven ) samples which have met the criteria. The analysis technique used is simple linear regression analysis. Based on the results of simple linear regression analysis with a significance level of 5% so that it shows the results of research namely that there is an influence of intellectual capital on the application of corporate governance in Islamic Commercial Banks in Indonesia.